Texas Aggies in Vietnam : War Stories - Lanning, Michael Lee (Book collections on Project MUSE., 2016)
From its inception, graduates of the Agricultural and Mechanical College of Texas, now Texas A & M University, have marched off to fight in every conflict in which the United States has been involved. The Vietnam War was no different. The Corps of Cadets produced more officers for the conflict in Southeast Asia than any institution other than the US service academies. Michael Lee Lanning, Texas A & M University class of 1968, has now gathered over three dozen recollections from those who served. As Lanning points out, "anytime Aggie Vietnam veterans get together-whether it is two or two hundred of.